ANALYSIS OF DIFFERENT MOUTH OPENINGS OF KNOCK-DOWN TRAPS IN SERANG WATERS, BANTEN - Daud, Moh. Ramadan; Sudrajat, Danu; Wibowo, Berbudi (Departemen PSP IPB, 2025)
Traps is a common fishing tool used by traditional fishers to catch demersal fish and reef fish. However, there are several problems related to the use of bubu in fishing. This study aims to test the effectiveness of knock-down traps in catching demersal fish and analyze the catch. This study compared two types of traps that have different mouth-opening sizes. This study used a Randomized Group Design (RAK) with two other treatments based on the size of the mouth opening. The fishing process was carried out with as many as 9 replicates or 9 trips. The research was conducted at three locations with different seabed characteristics. Bubu was installed for a month, then observations were made on the type, size, and weight of fish caught. The results showed that in both gear designs, there was a real effect on catches. The impact of Bubu with Bubu mouth opening size A is more effective in catching demersal fish than Bubu B. In Bubu A there were 131 fish caught weighing 71.7 kg, while Bubu B only produced 74 fish weighing 28.8 kg. There were 11 species of demersal fish caught with a greater variety of species in Bubu A, namely 11 species of fish, and in Bubu B as many as 6 species of fish. Key words: bubu mouth opening, effectiveness, demersal fish, catch